Improving the Marketing Approach in Managing Export-Oriented Distribution Channels - Usmonova Dilfuza Ilkhomovna; Tursunov Ozod (International Journal on Orange Technologies, 2021)
This article discusses the ways of developing the distribution activities of domestic producers in foreign markets. The features of the formation of the distribution policy using the marketing approach in management are revealed.